The Effect of Debt-to-Equity Ratio and Net Profit Margin on Dividend Payout Ratio at PT Mayora Indah Tbk During 2013-2024 - Fahira, Zahra Aulia; Akbar, Akhmad (Indonesian Financial Review, 2025)
This study examines the effect of capital structure and profitability on dividend policy at PT Mayora Indah Tbk during the 2013–2024 period. Using a quantitative approach with multiple regression analysis, the Debt to Equity Ratio (DER) represents capital structure, Net Profit Margin (NPM) measures profitability, and the Dividend Payout Ratio (DPR) reflects dividend policy. The results show that, partially, DER has a significant negative effect on DPR, indicating that higher leverage constrains dividend distribution. NPM also has a significant negative effect on DPR, suggesting that profitability is often retained as internal financing rather than distributed as dividends. Simultaneously, DER and NPM significantly affect DPR. The coefficient of determination of 54.9% indicates that more than half of dividend payout variation is explained by these variables. The findings highlight the strategic role of leverage and profitability in dividend policy decisions.